THEORETICAL REFERENCE OF THE P-MEDIANA PROBLEM AS A TOOL TO SUPPORT THE SUSTAINABILITY AND SOLUTION OF GEO-ENVIRONMENTAL PROBLEMS - José Fidelis de Azevedo, Claudio; de Oliveira Matias, Ítalo; Samahá Cordeiro, Tiago (LINKSCIENCEPLACE, 2026)
Nowadays, much is discussed about the importance of sustainability and the efficient management of environmental problems by public management. Waste of electrical energy, water waste, mosquitoes outbreaks, incorrect waste disposal, are just a few of the examples mentioned as environmental problems. It is of fundamental importance that there is efficiency in the management of these problems so that the population can use these resources in a responsible way, preserving them for future generations. In view of the above, a bibliometric study was developed with the objective of selecting a set of articles that can compose a theoretical reference that collaborates with the introduction of a researcher in this area of knowledge. The research was carried out on May 4, 2017 through the SCOPUS database, through the Portal of Periodicals of Capes, with the following selection criterion: ( ( p-median OR "facility location problem" OR "facilities location problem" ) AND ( geolocation OR sustainability ) ). The search was not performed only in the "Title of the article", "Summary" and "Keywords" fields, as SCOPUS database provides by default, but in all fields. Still in the selection criteria, the works published until the year 2016 were limited in order to keep the integrity of the research to the fullest in the future and did not account for publications after the period in which the research was carried out. The result of this research initially was 199 records. To compose the work, at the end of the research, 10 articles were selected resulting from the union of the application of the following rules: Identification of the journals with the largest number of articles published on the topic, identification of authors with the largest number of publications, Identifying "cycles of higher production" and selection of articles for composition of the "starting nucleus." These articles have the objective of assisting the researcher in the introduction of his studies on the application of the p-median problem in geolocalized points with environmental problems to Support efficient public management in this área.